2016
DOI: 10.2459/jcm.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular imaging in the diagnosis and monitoring of cardiotoxicity

Abstract: The evaluation by cardiovascular imaging of chemotherapy patients became a central topic in the last several years. The use of drugs for the treatment of cancers increased, and new molecules and protocols were developed to improve outcomes in these patients. Although, these novel approaches also produced a progressive increase in side effects, particularly myocardial dysfunction. Imaging of the heart was highly accurate in the early diagnosis of cancer therapeutics related-cardiac dysfunction. Echocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 90 publications
0
20
0
2
Order By: Relevance
“…In this study, it did not show significant differences between the two groups. Myocardial deformation indices of left ventricle (GLS) are known to be a very sensitive tool for the early detection of left ventricular dysfunction, and they have many advantages [19]. Several studies demonstrated that GLS is a predictor of cardiotoxicity.…”
Section: Color Version Available Onlinementioning
confidence: 99%
“…In this study, it did not show significant differences between the two groups. Myocardial deformation indices of left ventricle (GLS) are known to be a very sensitive tool for the early detection of left ventricular dysfunction, and they have many advantages [19]. Several studies demonstrated that GLS is a predictor of cardiotoxicity.…”
Section: Color Version Available Onlinementioning
confidence: 99%
“…The most frequently used parameter for routine cardiotoxicity monitoring is LVEF. A LVEF of >52% for men and >54% for women is considered normal . A LVEF drop of >10% or >5% with heart failure symptoms is considered diagnostic of cardiotoxicity.…”
Section: Role Of Imagingmentioning
confidence: 99%
“…Right ventricular dysfunction is rare, but some drugs such as anthracyclines, cyclophosphamide and 5-luouracil can cause right ventricular systolic and diastolic function [7]. It is important to be aware of the ofending agents in order to minimize exposure, if clinically possible, in a failing heart.…”
Section: Clinical Presentation and Initial Assessmentmentioning
confidence: 99%
“…If all structures are seen adequately during the irst echocardiogram, subsequent echocardiograms can be targeted function exams. The cardiac valves should be visualized on all exams as these patients have an increased risk of endocarditis, nonbacterial thrombotic endocarditis as well as radiation-induced heart disease afecting valves [7]. Transthoracic echocardiography is acceptable for looking for endocarditis if there are clear windows to the heart valves; otherwise depending on the index of suspicion, transoesophageal echocardiography is indicated as the gold standard.…”
Section: Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation